2021
DOI: 10.4081/monaldi.2021.1532
|View full text |Cite
|
Sign up to set email alerts
|

Hospital staff practical skills and theoretical knowledge in inhaled aerosol therapy: a single centre cross-sectional observational study

Abstract: Inhaled therapy is widely used for treatment of many respiratory disorders. Drug delivery in lungs is dependent on the correct use of aerosol devices and patients’ training is vital for a correct therapy administration. Therefore, is very important to assess the skills of professionals involved in training patients to the correct use of inhaler devices. The aim of this study was to check the practical skills and the theoretical knowledge of health care personnel in our University Hospital in using aerosol ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…At baseline, we obtained global poor results in theoretical and practical skills. In line with our findings, Santambrogio et al 6 found that the medium score in the evaluation of IT was 9.9 over a total score of 21 and that none of the participants answered correctly to all the theoretical questions. Similarly, Spaggiari et al 11 conducted a study in the PED, detecting that only 49% of participants did all the steps correctly in the practical examination and 34% almost perfectly.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…At baseline, we obtained global poor results in theoretical and practical skills. In line with our findings, Santambrogio et al 6 found that the medium score in the evaluation of IT was 9.9 over a total score of 21 and that none of the participants answered correctly to all the theoretical questions. Similarly, Spaggiari et al 11 conducted a study in the PED, detecting that only 49% of participants did all the steps correctly in the practical examination and 34% almost perfectly.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the most forgotten step in IT with spacer and mouthpiece was taking a deep exhalation before inhalation (75%) followed by exhaling slowly after inhalation (79.8%). Similar results were obtained in a systematic review by Plaza et al 10 However, in other studies, the most frequent errors were not breath‐holding after inhalation and not waiting a minute before the next inhalation 6 . These results are especially important, as identifying gaps in knowledge regarding proper IT is essential to impart continued education programs.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations